A G-protein-coupled receptor regulation pathway in cytochrome P450-mediated permethrin-resistance in mosquitoes, Culex quinquefasciatus - Li, Ting (Sci Rep, 2015)
Rhodopsin-like G protein-coupled receptors (GPCRs) are known to be involved in the GPCR signal transduction system and regulate many essential physiological processes in organisms. This study, for the first time, revealed that knockdown of the rhodopsin-like GPCR gene in resistant mosquitoes resulted in a reduction of mosquitoes’ resistance to permethrin, simultaneously reducing the expression of two cAMP-dependent protein kinase A genes (PKAs) and four resistance related cytochrome P450 genes. The function of rhodopsin-like GPCR was further confirmed using transgenic lines of Drosophila melanogaster, in which the tolerance to permethrin and the expression of Drosophila resistance P450 genes were both increased. The roles of GPCR signaling pathway second messenger cyclic adenosine monophosphate (cAMP) and downstream effectors PKAs in resistance were investigated using cAMP production inhibitor Bupivacaine HCl and the RNAi technique. Inhibition of cAMP production led to significant decreases in both the expression of four resistance P450 genes and two PKA genes and mosquito resistance to permethrin. Knockdown of the PKA genes had shown the similar effects on permethrin resistance and P450 gene expression. Taken together, our studies revealed, for the first time, the role of the GPCR/cAMP/PKA-mediated regulatory pathway governing P450 gene expression and P450-mediated resistance in Culex mosquitoes.